A Comparative Study on Urban Cruiser of Toyota V/S Harrier of Tata Engine, Mileage & Safety Among Consumers in Ahmedabad City - Tinwala, Mohammed; Singh, Vishal; Vidani, Jignesh (International Journal of Global Sustainable Research, 2024)
This study examines consumer preferences regarding the Toyota Urban Cruiser and Tata Harrier with a focus on engine performance, mileage, and safety features in Ahmedabad City. Through hypothesis testing, the research explores how factors such as age influence perceptions and decisions when choosing between these two popular vehicles. Results indicate that there are significant associations between respondents' age and their beliefs about the engine performance of the Toyota Urban Cruiser, the luxury features of the Tata Harrier, and their fuel efficiency and city suitability. The study finds that older consumers tend to prioritize aspects such as engine reliability, smoothness, and practical performance, while younger consumers place more value on advanced technology and premium features. Additionally, the study highlights a shift in consumer preferences where younger buyers gravitate toward the luxury, design, and technology offered by the Tata Harrier, while older buyers prefer the comfort and efficiency of the Toyota Urban Cruiser. The research contributes to understanding the diverse needs of consumers in the automotive sector, offering insights for marketing strategies, product development, and customer engagement. The findings suggest that automakers can benefit from age-specific targeting, optimizing their products and advertising to meet the preferences of distinct consumer segments